Development and qualification of a new polymeric matrix laminated composite for pipe repair. (15th September 2016) - Rohem, N.R.F.; Pacheco, L.J.; Budhe, S.; Banea, M.D.; Sampaio, E.M.; de Barros, S.
Abstract: Nowadays the use of polymeric matrix composites to repair and strengthen the damaged pipe structures in the oil industry has become a common practice. Hence, it is essential to validate the performance of new developed composite laminate materials for the damaged pipe repair. In this study, the effectiveness of a new composite laminate for the pipes repair was investigated. First, the mechanical and thermal properties of the new developed composite laminate were determined. Next, two defect types, Type A (non-through wall) and Type B (through wall) were manufactured into the pristine pipe specimen and the evaluation of the performance of the repaired pipe was carried out by hydrostatic tests. The performance of the repaired pipe using the new developed composite laminate material was satisfactory in both defect types.